Parenting in patients with borderline personality disorder, sequelae for the offspring and approaches to treatment and prevention - Florange, Julian G.; Herpertz, Sabine (Current psychiatry reports, 2019)
Purpose of ReviewWe review recent findings concerning the implications of borderline personality disorder (BPD) on parenting behaviors, the parent-child relationships, and parental and child outcomes. We focus on self-report and interview data characterizing parents with BPD and their children as well as on observational paradigms investigating parent-child relationships and the quality of dyadic interactions. Novel treatment approaches are discussed.Recent FindingsParents with BPD suffer from increased parenting stress and display characteristic behavioral patterns towards their children, impeding the formation of a healthy parent-child relationship and disrupting offspring emotional development. Offspring are at greater risk of maltreatment and developing BPD themselves, with parental affective instability playing a substantial mediating role.SummaryMothers with BPD face a meaningful burden in their parenting role. Mechanisms of the transmission of BPD pathology onto the following generation are beginning to be understood. Targeted interventions have been devised recently, with preliminary testing producing encouraging results.